PRACTICAS DE LABORATORIOS DE FARMACOTECNIA Y FARMACIA MAGISTRAL EN REGENCIA DE FARMACIA - Restrepo Zapata, Jorge Humberto; Cuadros Gutierrez, Diego Gerardo; Rosero Ramos, Anyell Melissa; Díaz González, Diana Marcela; Almendra Vidal, Jhon Edduar; Burbano Portilla, María Alejandra; Parra Gutiérrez, Marisol (Universidad Santiago de Cali, 2025)
Pharmacotechnology and Compound Pharmacy comprise the study of the scientific and methodological bases for addressing and carrying out the operations that are necessary in the development of the technological processes that lead to the production of pharmaceutical forms: preformulation studies, properties of excipients, basic operations and selection and design of the pharmaceutical form. Basic prior knowledge of the intrinsic properties of drugs, their therapeutic activity and the characteristics of the different routes of administration of medicines (Physical Chemistry, Pharmacology and Biopharmacy and Pharmacokinetics) is required. From Pharmacotechnology and Magistral Pharmacy, the technological processes that allow the elaboration of magistral and industrial products of medicines for conventional oral and parenteral administration are addressed, as well as the different tests and controls that guarantee the correct elaboration and / or manufacturing in accordance with the standards established in the Pharmacopoeias accepted in the country and that enable the pharmaceutical products to develop their professional activity in the different areas of their performance.